Virtual Biology Laboratory Training for High School Biology Teachers and Laboratory Technicians in Yogyakarta - Aji, Oktira Roka; Pratiwi, Ambar; Suwartiningsih, Nurul; Astuti, Sutan Nur Chamida Tri; Irsalinda, Nursyiva (Jurnal Abdimas, 2024)
As the COVID-19 pandemic comes to an end, education has returned to normal with in-person learning. The good practices in online learning conducted during the pandemic can be maintained to support practical activities, for example, using a virtual laboratory. The limitations of laboratory facilities and the skills of educators and laboratory staff in developing practical materials have made Biology practicals minimal and monotonous. Based on discussions with partners, there is a main problem that needs to be addressed through this program, which is the limited laboratory facilities in terms of tools and materials, resulting in minimal implementation of Biology practical activities in schools. The objective of this community service is to enhance the knowledge, skills, and empowerment of Biology teachers at Muhammadiyah high schools in Yogyakarta City in conducting practicals using virtual labs. This community service method is carried out by training on Biology practical learning online using virtual labs. This program is conducted in several sessions, each lasting 200 minutes, from June to October. Each session consists of a pre-test, material delivery, Q&A discussions, and a post-test. It can be concluded that the community service activities ran smoothly and provided benefits in the form of increased knowledge and skills of participants in Biology practical learning using virtual labs.